2014
DOI: 10.2215/cjn.13031213
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Effects of Exercise Training in CKD

Abstract: Cardiovascular disease remains the main cause of morbidity and mortality in patients with CKD, an observation that cannot be explained by the coexistence of traditional risk factors alone. Recently, other mechanisms, such as alterations in nitric oxide bioavailability, impaired endothelial repair mechanisms, inflammation, and oxidative stress (all characteristic in CKD), have gained much attention as mediators for the increased cardiovascular risk. Regular physical training is a valuable nonpharmacological int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 71 publications
3
29
2
1
Order By: Relevance
“…A late-onset decrease in oxidative stress and increase in anti-oxidative factors due to exercise training could prevent progressive fibrosis in the kidneys [ 47 , 48 ]. Exercise-induced blood volume expansion likely contributes to increased renal blood flow and shear stress in the kidney at rest and during exercise [ 49 – 51 ], the latter stimulating improvements in endothelial function [ 52 ]. However, Van Craenenbroeck et al [ 26 ] and Headley et al [ 27 ] reported no effect on flow-mediated dilation in patients with CKD stages 3–4 after a 12 and 16 weeks aerobic training regimen respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A late-onset decrease in oxidative stress and increase in anti-oxidative factors due to exercise training could prevent progressive fibrosis in the kidneys [ 47 , 48 ]. Exercise-induced blood volume expansion likely contributes to increased renal blood flow and shear stress in the kidney at rest and during exercise [ 49 – 51 ], the latter stimulating improvements in endothelial function [ 52 ]. However, Van Craenenbroeck et al [ 26 ] and Headley et al [ 27 ] reported no effect on flow-mediated dilation in patients with CKD stages 3–4 after a 12 and 16 weeks aerobic training regimen respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity can partially if not almost fully be explained by between-study differences in age and BMI. Even though training modalities are determinants of treatment effects sizes for CV outcomes in patients with CKD [ 52 ], nor analyses on training type and duration nor differences in supervision, frequency or intensity of training could explain the high heterogeneity. However, exclusion of the four studies using both aerobic and resistance exercise training also resulted in a negligible heterogeneity (I 2 = 19%).…”
Section: Discussionmentioning
confidence: 99%
“…As with most populations, regular exercise is reported to have numerous benefits for early CKD, HD and transplant patients. These include improved exercise capacity, quality of life and cardiovascular health [12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Patients on HD are subject to at least 12-h of physical inactivity per week and show poor levels of physical activity on both dialysis and non-dialysis days compared to healthy subjects and kidney transplant recipients [22]. Accordingly, HD itself promotes the vicious circle of physical inactivity and impaired exercise capacity [23]. Physical activity has been recognized as a major treatable aspect in patients with high CV risk and results in improved physical performance and prognosis [24,25].…”
Section: Discussionmentioning
confidence: 99%